2015
DOI: 10.1016/j.envsoft.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Feature-preserving interpolation and filtering of environmental time series

Abstract: a b s t r a c tWe propose a method for filling gaps and removing interferences in time series for applications involving continuous monitoring of environmental variables. The approach is non-parametric and based on an iterative pattern-matching between the affected and the valid parts of the time series. It considers several variables jointly in the pattern matching process and allows preserving linear or non-linear dependences between variables. The uncertainty in the reconstructed time series is quantified t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In this paper, we propose a non-parametric method to simulate missing data 20 inside flow rate time-series based on the Direct Sampling (DS) technique Ma-riethoz et al (2010) belonging to multiple-point statistics (MPS). Already tested on gap filling in multivariate data sets representing natural heterogeneities Mariethoz et al (2012Mariethoz et al ( , 2015 and on rainfall time-series simulation Oriani et al (2014), DS can simulate the outcome of a complex natural pro-25 cess by reproducing similar patterns to the ones found in the available data without imposing a specific statistical model. More particularly, missing data are simulated by sampling the available data set where a sufficiently similar pattern is found.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we propose a non-parametric method to simulate missing data 20 inside flow rate time-series based on the Direct Sampling (DS) technique Ma-riethoz et al (2010) belonging to multiple-point statistics (MPS). Already tested on gap filling in multivariate data sets representing natural heterogeneities Mariethoz et al (2012Mariethoz et al ( , 2015 and on rainfall time-series simulation Oriani et al (2014), DS can simulate the outcome of a complex natural pro-25 cess by reproducing similar patterns to the ones found in the available data without imposing a specific statistical model. More particularly, missing data are simulated by sampling the available data set where a sufficiently similar pattern is found.…”
Section: Introductionmentioning
confidence: 99%
“…The Lomb‐Scargle PSD offers an alternative approach to dealing with data gaps to that proposed by Mariethoz et al . []. It also allowed determination of the probability of a certain frequency peak being related to a real periodic signal and not the result of random fluctuations; i.e., the probability of detection [ Trauth , ].…”
Section: Methodsmentioning
confidence: 99%
“…The Lomb-Scargle PSD, a least squares spectral analysis technique, was chosen because it can be used with time series data that have gaps or that are not evenly spaced in time [Lomb, 1976;Trauth, 2010]. The Lomb-Scargle PSD offers an alternative approach to dealing with data gaps to that proposed by Mariethoz et al [2015]. It also allowed determination of the probability of a certain frequency peak being related to a real periodic signal and not the result of random fluctuations; i.e., the probability of detection [Trauth, 2010].…”
Section: Spectral Analysis Methodsmentioning
confidence: 99%
“…Finally, we median filter the resulting time-series using a 1-hour window corresponding to the time-interval used to represent the SP data in this paper. See Mariethoz et al (2015) for an alternative data processing approach that has been demonstrated for a sub-set of the presented data.…”
Section: Self-potential Datamentioning
confidence: 99%